Some Personal and Situational Correlates of Reactions to Management Development Training: Reply - Carroll, Stephen J.; Nash, Allan N. (Academy of Management Journal, 1970)
The article reports the authors' opinions regarding a criticism of their article ?Some Personal and Situational Correlates of Reactions to Management Development Training.? The authors' focus on comments made about the purpose and content of management development programs. Possible reasons that executives might have for supporting or opposing management training programs are also discussed.